Analysis of religious moderation values in students' extracurricular religious guidance activities - Rahilah Supina Nst; Kholidah Nur; Yuni Sarah (Inovasi Kurikulum, 2025)
In education, religious moderation is considered an approach to building harmony, tolerance, and mutual respect among religious communities. This study explores the values of religious moderation in extracurricular activities for the religious development of students at SMA Negeri 2 Padangsidimpuan. This study uses a qualitative approach with a descriptive method, collecting data through interviews with school officials and students who actively participate in religious extracurricular activities. The research results show that the values of religious moderation in schools include a commitment to nationalism, tasamuh (tolerance), i'tidal (justice), shura' (deliberation), and anti-violence. Implementing the values of religious moderation begins with the internalization of values through three stages: value transformation, value transaction, and value transinternalization. The supervisor evaluates the members of religious extracurricular activities to determine the extent to which the values of religious moderation are applied. The results of applying these values in extracurricular activities to develop students' religion are reflected in attitudes of care, helpful deliberation, and justice in words and deeds. The importance of religious moderation in promoting harmony, mutual respect, and tolerance among students can develop a more loving and respectful environment.   Abstrak Pada konteks pendidikan, moderasi beragama dianggap sebagai pendekatan untuk membangun harmoni, toleransi, dan saling menghormati antar umat beragama. Studi ini bertujuan untuk mengeksplorasi nilai-nilai moderasi beragama dalam kegiatan ekstrakurikuler untuk pengembangan keagamaan siswa di SMA Negeri 2 Padangsidimpuan. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, mengumpulkan data melalui wawancara dengan pejabat sekolah dan siswa yang aktif berpartisipasi dalam kegiatan ekstrakurikuler keagamaan. Hasil penelitian menunjukkan bahwa nilai-nilai moderasi beragama di sekolah mencakup komitmen kebangsaan, tasamuh (toleransi), i'tidal (keadilan), shura' (musyawarah), dan anti-kekerasan. Proses penerapan nilai-nilai moderasi beragama dimulai dengan proses internalisasi nilai dengan tiga tahap: transformasi nilai, transaksi nilai, dan transinternalisasi nilai. Pengawas melakukan evaluasi terhadap anggota ekstrakurikuler keagamaan untuk menentukan sejauh mana nilai-nilai moderasi beragama diterapkan. Hasil penerapan nilai-nilai ini dalam kegiatan ekstrakurikuler untuk pengembangan agama siswa tercermin dalam sikap peduli, musyawarah yang membantu, dan keadilan baik dalam kata-kata maupun perbuatan. Pentingnya moderasi agama dalam mempromosikan harmoni, saling menghormati, dan toleransi antara siswadapat mengembangkan lingkungan yang lebih penuh kasih dan saling menghormati. Kata Kunci: ekstrakurikuler keagamaan; moderasi beragama; pembinaan keagamaan